Twenty-Four-Hour Contact Lens Sensor Monitoring of Aqueous Humor Dynamics in Surgically or Medically Treated Glaucoma Patients - Chiara Posarelli; Pierluigi Ortenzio; Antonio Ferreras; Mario Domenico Toro; Andrea Passani; Pasquale Loiudice; Francesco Oddone; Giamberto Casini; Michele Figus (Journal of Ophthalmology)
Aim. This study assessed the 24 h circadian rhythm of intraocular pressure (IOP) using a contact lens sensor in three groups of patients with open-angle glaucoma. Methods. This study was a monocentric, cross-sectional, nonrandomized, prospective, pilot study. Eighty-nine patients were enrolled: 29 patients previously underwent an Ex-PRESS mini glaucoma device procedure (Group 1), 28 patients previously underwent Hydrus microstent implantation (Group 2), and 32 patients were currently being treated medically for primary open-angle glaucoma (Group 3). Circadian rhythm patterns were considered with five circadian indicators: fluctuation ranges, maximum, minimum, acrophase (time of peak value), and bathyphase (time of trough value). A two-tailed Mann–Whitney U-test was used to evaluate differences between groups. Results. All subjects exhibited a circadian rhythm and a nocturnal pattern. The signal fluctuation range was significantly smaller in the surgical groups than in the medically treated group (Group 1 vs. Group 3, p=0.003; Group 2 vs. Group 3, p=0.010). Subjects who underwent the Ex-PRESS procedure (Group 1) exhibited significant differences compared with the drug therapy group (Group 3) with regard to the minimum value (p=0.015), acrophase (p=0.009), and bathyphase (p=0.002). The other circadian indicators were not significantly different among groups. Conclusions. Patients who underwent IOP-lowering surgery had an intrinsic nyctohemeral rhythm. Both surgical procedures, Ex-PRESS and Hydrus, were associated with smaller signal fluctuations compared with medical treatment.